PEMBUATAN PERCONTOHAN KERAMBA JARING APUNG (KJA) RAMAH LINGKUNGAN DI PERAIRAN DANAU - Jaya, N.M.P.; Harmayani, K.D.; Widhiawati, I.A.R.; Parahita, I.G.A.A.; Wiryananda, N.G.A.K.; Putra, I.N.A.G.P.; Praniti, A.A.I.; Tara, N.P.R.S. (Buletin Udayana Mengabdi, 2023)
Cultivating freshwater fish using floating net cages (KJA) causes an increase in the nutrient content of uneaten feed and fish feces. Making a KJA pilot using aquatic plant biofilters capable of absorbing pollutants and of economic value, such as water spinach, bok choy, and red spinach, is carried out to socialize pollution from KJA activities and water quality management. The implementation of activities applies the Participatory Learning and Action (PLA) method by involving the Fish Farmers Group in Lake Batur in designing and installing environmentally friendly KJA. The KJA system consists of 3 (three) principal components, i.e., a watertight pond, a reservoir for leftover feed waste, and aquaponic plants. The community can understand the pollution and the importance of managing water quality based on the evaluation results. Besides that, through the direct involvement of the community, the design and application of KJA were produced following the conditions of the waters in Lake Batur. This relates to the layout of the components, namely the placement of a window for water circulation between the KJA pond and lake waters in a watertight pond, the order of a tank to hold leftover feed and fish feces as a result of suction from the bottom of the pond in the middle of the KJA, and the planting of plants in the planting medium pipe on the side of the KJA pond. Besides being helpful in environmental management, this KJA installation can be useful for increasing the economy through plant cultivation. Keywords: Aquaculture, Participatory Learning and Action (PLA), Lake Batur Waters, Environmentally Friendly Floating Net Cages (KJA), Water Quality Management.